The world almanac and book of facts, 2012 - Janssen, Sarah , 1982- (World Almanac Books, 2012)
Presents comprehensive facts and statistics on current events, people, and the countries of the world, along with original articles on recent issues and topics ranging from the 2012 presidential candidates to the 2011 World Series and Women's World Cup